Pairing-free certificateless blockchain-based access authentication method for spatial information network - HUO Ru; WANG Zhihao; SHAO Zihao; HUANG Tao (Tongxin xuebao)
Due to the single point failure and opaque certificate distribution process of the access authentication methods in a traditional terrestrial network, it was difficult to apply to a spatial information network with a highly complex and dynamic topology. Therefore, pairing-free certificateless blockchain-based access authentication method for spatial information network was proposed. Firstly, a satellite-blockchain network communication model was constructed, combining consortium blockchain and certificateless public key cryptography distribution technology. Furthermore, a certificateless public key without pairing and elliptic curve hybrid encryption algorithm based on blockchain was proposed, and an access authentication mechanism was designed to ensure the security of the access authentication process and the traceability of operations. Finally, the access authentication list was recorded through the extended block structure, and the batch verification mechanism was designed to achieve efficient handover. Security analysis and simulation results show that, compared with existing methods, the proposed method reduces the signaling overhead by about 50%, the authentication delay by at least 12.4%, and the batch authentication delay by about 23%, while providing stronger security guarantees.